Preferensi Pemilihan Laptop Desainer Grafis Melalui Analisis Konjoin - Al Muktafie, Ahmad Faqih; Setiawan, Tabah Heri; Aden, Aden; Basir, Choirul (Jurnal Matematika, 2025)
The development of technology and the graphic design industry is increasing, creating a variety of laptop specifications. This research aims to identify graphic designers' preferences in choosing a graphic design laptop. The background of this research is the complexity of laptop specifications that continue to grow and the various considerations that need to be considered by graphic designers in choosing the appropriate laptop. The conjoin analysis method is used in collecting data related to graphic designers' preferences for laptops for graphic design. Then, the data was analyzed to identify the most influential attributes of laptop selection. The results stated that the RAM capacity attribute dominated graphic designers' preferences when choosing a laptop for graphic design, with a percentage of importance value of 41.78%. Then, price (26.11%), screen resolution (18.06%), VGA (12.09%), and processor (1.96%) also contributed significantly to laptop selection. The most preferred combination by graphic designers is a laptop with 16GB RAM capacity, price <IDR10,000,000, UHD (ultra high definition) screen resolution, NVIDIA VGA, and Intel processor. The findings have practical implications for graphic designers, who can use the results of this study to make more informed decisions when purchasing a laptop. In addition, the conjoin analysis method can also be applied to understanding consumer preferences in many fields.